A kind of acid corrosion resistant material for cementing and its preparation method and application

By using modified alkaline magnesium sulfate whiskers, calcined magnesium-aluminum carbonate hydrotalcite and other materials in cement slurry, the corrosion problem of acid gas on the cement ring is solved, and the corrosion resistance of cement stone and its overall performance are improved. , ensuring the safety and production stability of the wellbore.

CN118771772BActive Publication Date: 2024-12-13SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411270234.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

When the prior art faces acidic oil and gas resources with high H2S and CO2 content, it is difficult to effectively prevent the acidic gas from corrosion on the cement ring, resulting in sealing failure, affecting the integrity of the wellbore and safe production.

Method used

Using modified alkaline magnesium sulfate whiskers, calcined magnesium-aluminum carbonate hydrotalcite, silicon carbide fibers and nano-silica powder, the anti-acid corrosion resistance with acid gas corrosion resistance is prepared through ultrasonic dispersion and calcination treatment. Material, used to prepare cement slurry, improve the density and corrosion resistance of cement stone.

Benefits of technology

It significantly improves the corrosion resistance of cement stones against acid gases, reduces the permeability and porosity of cement slurry, extends the sealing capacity of cement rings, and reduces the attenuation rate of pure cement systems by 38.19%, and does not affect the compressive strength. In the case of this, the overall performance of cement slurry is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118771772B_ABST
    Figure CN118771772B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of oil and gas well cementing materials, and in particular to an acid corrosion resistant material for cementing, a preparation method and an application thereof, comprising modified basic magnesium sulfate whiskers, calcined magnesium aluminum carbonate type hydrotalcite, silicon carbide fiber and a binder in a mass ratio of 1-2:0.5-1:1-2:1-2, wherein the binder is one or two of nano silicon dioxide powder and latex powder. The present invention adopts the above-mentioned acid corrosion resistant material for cementing, a preparation method and an application thereof, and after the prepared acid corrosion resistant material is used to prepare cement slurry, the formed cement stone has the ability to resist corrosion by carbon dioxide and hydrogen sulfide acid gases, thereby ensuring that the cement sheath maintains long-term sealing ability in a carbon dioxide and hydrogen sulfide gas environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas well cementing materials, and in particular to an acid corrosion resistant material for cementing, a preparation method and application thereof. Background Art

[0002] With the continuous deepening of oil and gas resource exploration and development, many acidic oil and gas resources with high H2S and CO2 content have been included in the development focus. However, acidic corrosive media such as H2S and CO2 in acidic oil and gas will have leaching and synergistic effects with oil well cement, reducing the alkalinity of cementing cement, resulting in a reduction in cementing components in cement, destruction of pore structure, increased permeability, reduced compressive strength or even complete loss, so that the cement ring loses its sealing performance, causing sealing failure, prone to annular pressure, gas channeling at the wellhead, affecting the integrity of the wellbore, and bringing hidden dangers to the safe production of oil and gas wells. At the same time, H2S is a highly toxic gas, which will rise to the ground and affect the safety of surrounding life, property and environment.

[0003] In view of the above safety hazards, the existing technologies mostly use external additives to reduce the alkalinity of silicate cement or add external additives such as latex to reduce the permeability of silicate cement paste, or a combination of the two. However, these technologies can only inhibit the corrosion of CO2-corroded cement sheaths, and have poor corrosion resistance against acidic gas H2S. In the complex formation environment, cement slurry system technologies that can effectively prevent acidic gas corrosion for a long time are still rare. Therefore, it is of great significance to develop corresponding anti-acidic gas corrosion materials and apply them to cement slurries. Summary of the invention

[0004] The purpose of the present invention is to provide an acid corrosion resistant material for cementing, a preparation method and application thereof. After the prepared acid corrosion resistant material is used to prepare cement slurry, the formed cement stone has the ability to resist acid gas corrosion, ensuring that the cement sheath maintains long-term sealing ability in an acid gas environment.

[0005] To achieve the above-mentioned purpose, the present invention provides an acid corrosion resistant material for cementing, comprising modified basic magnesium sulfate whiskers, calcined magnesium aluminum carbonate type hydrotalcite, silicon carbide fiber and a binder in a mass ratio of 1~2:0.5~1:1~2:1~2, wherein the binder is one or both of nano silicon dioxide powder and latex powder.

[0006] Preferably, the particle size of the modified basic magnesium sulfate whisker is 1000-2000 mesh, the particle size of the calcined magnesium aluminum carbonate type hydrotalcite is 1000-2000 mesh, the particle size of the silicon carbide fiber is 1000-2000 mesh, and the particle size of the binder is 1000-2000 mesh.

[0007] A method for preparing an acid corrosion resistant material for cementing comprises the following steps:

[0008] S1. Preparation of modified basic magnesium sulfate whiskers

[0009] S1.1, mixing anhydrous ethanol and deionized water to prepare a mixed solution as a modified solvent;

[0010] S1.2, add silane coupling agent to the modified solvent, ultrasonically disperse for 30 minutes, adjust the pH with anhydrous oxalic acid, then add basic magnesium sulfate whisker, ultrasonically disperse for 2-3 hours, and heat the reaction to obtain a milky white gel liquid;

[0011] S1.3 Wash, purify and dry the milky white gel liquid with anhydrous ethanol, grind and sieve the dried powder to obtain modified basic magnesium sulfate whiskers;

[0012] S2. Preparation of calcined magnesium aluminum carbonate type hydrotalcite

[0013] The magnesium aluminum carbonate type hydrotalcite is dried in an oven, and then transferred to a muffle furnace for calcination. After cooling to room temperature in the furnace, the calcined magnesium aluminum carbonate type hydrotalcite is obtained by ball milling and sieving.

[0014] S3. Preparation of acid corrosion resistant materials

[0015] The modified basic magnesium sulfate whisker prepared by S1, the calcined magnesium aluminum carbonate type hydrotalcite prepared by S2, silicon carbide fiber and a binder are uniformly mixed to obtain an acid corrosion resistant material.

[0016] Preferably, the volume ratio of anhydrous ethanol to deionized water in S1.1 is 2-5:1.

[0017] Preferably, the amount of silane coupling agent in S1.2 is 30% to 50% of the mass of the basic magnesium sulfate whisker, the pH range is 4.0 to 5.0, and the heating reaction is condensed and refluxed at a speed of 500-800 r / min for 3 hours at a temperature of 65°C.

[0018] Preferably, the drying in S1.3 is performed in a thermostat at 60° C. for 24 h, the grinding is performed in a ball mill for 2 to 3 h, the rotation speed is 600-800 r / min, the mass ratio of powder, balls and water in the ball mill is 1:1:0.5, and the sieving is performed through a 1000-2000 mesh sieve.

[0019] Preferably, the oven drying in S2 is drying at 105° C. for 24 hours, and the calcination is heating in an electric furnace at a heating rate of 10 to 20° C. / min to 500° C. and maintaining the temperature for 2 to 4 hours.

[0020] Preferably, the ball milling in S2 is wet milling in a ball mill for 2-3 hours at a rotation speed of 600-800 r / min, the mass ratio of powder, balls and water in the ball mill is 1:1:0.5, and the sieving is through a 1000-2000 mesh sieve.

[0021] The invention discloses an application of an acid corrosion resistant material for cementing, which is applied to preparing cement slurry for cementing.

[0022] Preferably, the preparation of cement slurry for cementing is as follows: take oil well cement and anti-acid corrosion material and mix them evenly to obtain a dry powder mixture; weigh water, dispersant, fluid loss agent, defoamer, and retarder, first pour the water into the mixing cup of the constant speed stirrer, set the speed to 1500 r / min, stir at low speed for 15 s, during which time slowly and evenly pour the dry powder mixture, dispersant, fluid loss agent, defoamer and retarder, then adjust the speed to 4000 r / min, stir at medium speed for 45 s, and finally adjust the speed to 6000 r / min, stir at high speed for 30 s, and end the stirring to complete the slurry preparation.

[0023] Beneficial effects of the present invention:

[0024] (1) The present invention adds a filler-type anticorrosion agent, modified basic magnesium sulfate whisker, silicon carbide fiber, and an inducing hydration product-type anticorrosion agent, calcined magnesium aluminum carbonate-type hydrotalcite, to the material for preventing carbon dioxide and hydrogen sulfide corrosion, and uses anticorrosion admixtures with different action mechanisms in combination, thereby improving the densification effect of the anti-acid corrosion material, consuming CH to induce the formation of CASH while filling the cement stone matrix, and improving the cement stone's ability to resist acid gas corrosion.

[0025] (2) The modified magnesium sulfate whiskers are used to improve their stability and enable them to better adapt to the complex underground environment. Compared with ordinary magnesium carbonate whiskers, the modified silane coupling agent introduces a hydrophobic organic part, which transforms it from a highly hydrophilic substance to a slightly less hydrophilic substance, thereby improving its dispersibility. After being ground, the modified magnesium sulfate whiskers have smaller particle size and can be filled in the pores of the cement matrix, thereby improving the density of the matrix and thus improving the cement stone's resistance to acidic gas corrosion.

[0026] (3) Compared with ordinary magnesium aluminum carbonate hydrotalcite, the calcined magnesium aluminum carbonate hydrotalcite has a larger specific surface area and pore volume, and has a stronger adsorption capacity, which improves the disadvantage of poor dispersibility of ordinary hydrotalcite in cement slurry. In addition, the calcined magnesium aluminum carbonate hydrotalcite has a "memory effect". After being added to the cement slurry, the structure will be reconstructed and the original layered characteristic structure of the hydrotalcite will be restored. At the same time, the calcined magnesium aluminum carbonate hydrotalcite is also a non-toxic and harmless environmentally friendly substance.

[0027] (4) The acid corrosion resistant material provided by the present invention reduces the alkaline components in cement slurry, increases the density of cement paste, and improves the corrosion resistance of cement paste through the interaction between different components. Compared with the pure cement system, the attenuation rate is relatively reduced by 38.19%.

[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the SEM image of ordinary cement slurry in comparative example 1. Figure 1 (a) is the SEM image of the cement sample of comparative example 1 after curing for 7 days. Figure 1 (b) is the inner layer sample of comparative example 1 after corrosion for 60 days. Figure 1 (c) is the outer layer sample of Comparative Example 1 after corrosion for 60 days;

[0030] Figure 2 This is the SEM image of the ordinary cement slurry in Example 1. Figure 2 (a) is the SEM image of the cement sample after curing for 7 days in Example 1. Figure 2 (b) is the inner layer sample after 60 days of corrosion in Example 1. Figure 2 (c) is the outer layer sample of Example 1 after corrosion for 60 days;

[0031] Figure 3 This is the SEM image of the ordinary cement slurry in Example 2. Figure 3 (a) is the SEM image of the cement sample after curing for 7 days in Example 2. Figure 3 (b) is the inner layer sample after 60 days of corrosion in Example 2. Figure 3 (c) is the outer layer sample of Example 2 after corrosion for 60 days;

[0032] Figure 4 This is the SEM image of the ordinary cement slurry of Example 3. Figure 4 (a) is the SEM image of the cement sample after curing for 7 days in Example 3. Figure 4 (b) is the inner layer sample after 60 days of corrosion in Example 3. Figure 4 (c) is the outer layer sample of Example 3 after corrosion for 60 days;

[0033] Figure 5 is the pore size distribution curve of the cement slurry system of the present invention, Figure 5 (a) is the pore size distribution curve of the ordinary cement slurry system in comparative example 1, Figure 5 (b) is a pore size distribution curve of cement slurry for cementing in Example 1. Figure 5 (c) is a pore size distribution curve of cement slurry for cementing in Example 2. Figure 5 (d) is a pore size distribution curve of the cement slurry for cementing in Example 3. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with the accompanying drawings and embodiments. Unless otherwise defined, the technical terms or scientific terms used in the present invention should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs. The above-mentioned features or features mentioned in the specific examples mentioned in the present invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0035] Sources of materials used in the examples of the present invention

[0036] The oil well cement uses Sichuan Jiahua G-grade high sulfur resistance oil well cement;

[0037] The fluid loss reducer is the "Fluid Loss Reducer for Oil Well Cement G33S" which is publicly available on the market by Weihui Chemical Co., Ltd. and meets the above-mentioned petroleum industry standards;

[0038] The drag reducer is the "drag reducer for oil well cement USZ" sold on the market by Weihui Chemical Co., Ltd. and in compliance with the above-mentioned petroleum industry standards;

[0039] The retarder is selected from organic acid DRH and organic acid JXH produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.

[0040] The defoamer used was "Oil Well Cement Defoamer DF-T" which is publicly available on the market by Weihui Chemical Co., Ltd.

[0041] Example 1

[0042] The invention provides an acid corrosion resistant material for cementing, comprising 1000-mesh modified basic magnesium sulfate whisker, 1000-mesh calcined magnesium aluminum carbonate type hydrotalcite, 2000-mesh silicon carbide fiber and 2000-mesh nano silicon dioxide powder in a mass ratio of 1:1:1:1.

[0043] The method for preparing the above-mentioned acid corrosion resistant material for cementing comprises the following steps:

[0044] S1. Preparation of modified basic magnesium sulfate whiskers

[0045] S1.1. Anhydrous ethanol and deionized water are mixed in a volume ratio of 3:1 to prepare a mixed solution as a modified solvent.

[0046] S1.2. Add 30% of silane coupling agent based on the mass of ordinary basic magnesium sulfate whisker (300 mesh) to 200 mL of modified solvent, and after ultrasonic dispersion for 30 minutes, use anhydrous oxalic acid to adjust the pH to about 4.5, and then add basic magnesium sulfate whisker (300 mesh). After ultrasonic dispersion for 2 hours, transfer to a 500 mL flask, condense and reflux at 65°C at a speed of 500 r / min for 3 hours to obtain a milky white gel liquid.

[0047] S1.3. Wash and purify the milky white gel liquid with anhydrous ethanol to remove unreacted coupling agent, then filter it and dry it in a constant temperature oven at 60°C for 24 hours. Put the dried powder, grinding balls and water in a ball mill at a mass ratio of 1:1:0.5 for wet grinding for 2 hours at a speed of 600r / min. After grinding, take it out and pass it through a 1000-mesh sieve to obtain modified basic magnesium sulfate whiskers.

[0048] S2. Preparation of calcined magnesium aluminum carbonate type hydrotalcite

[0049] The magnesium aluminum carbonate type hydrotalcite was dried in an oven at 105°C for 24 hours, then placed in a muffle furnace, heated to 500°C at a heating rate of 10°C / min and kept at a constant temperature for 4 hours. After cooling to room temperature with the furnace, the powder, grinding balls and water were put into a ball mill at a mass ratio of 1:1:0.5, wet-milled for 2 hours at a rotation speed of 600r / min, and taken out after grinding and passed through a 1000-mesh sieve to obtain calcined magnesium aluminum carbonate type hydrotalcite.

[0050] S3. Preparation of acid corrosion resistant materials

[0051] The modified basic magnesium sulfate whisker prepared by S1, the calcined magnesium aluminum carbonate type hydrotalcite prepared by S2, silicon carbide fiber and nano silicon dioxide powder are uniformly mixed to obtain an acid corrosion resistant material.

[0052] The above-mentioned acid corrosion resistant material for cementing is used in preparing cement slurry for cementing.

[0053] The preparation of cement slurry for cementing is as follows: 100 parts of oil well cement and 2 parts of anti-acid corrosion material are mixed evenly to obtain a dry powder mixture; 44 parts of water are weighed, 0.2 parts of dispersant USZ, 0.2 parts of fluid loss reducer G33S, 0.1 parts of defoamer, and 0.1 parts of retarder are added, and the water is first poured into the stirring cup of the constant speed stirrer, and the speed is set to 1500r / min, and stirred at a low speed for 15s. During this period, the dry powder mixture, dispersant, fluid loss reducer, defoamer and retarder are slowly and evenly poured in, and then the speed is adjusted to 4000r / min, and stirred at a medium speed for 45s. Finally, the speed is adjusted to 6000r / min, and stirred at a high speed for 30s. After the stirring is completed, the slurry is prepared to obtain cement slurry for cementing that resists acid gas corrosion.

[0054] Example 2

[0055] The invention provides an acid corrosion resistant material for cementing, comprising 1500-mesh modified basic magnesium sulfate whisker, 1000-mesh calcined magnesium aluminum carbonate type hydrotalcite, 2000-mesh silicon carbide fiber and 1000-mesh latex powder in a mass ratio of 1:0.5:1:1.

[0056] The method for preparing the above-mentioned acid corrosion resistant material for cementing comprises the following steps:

[0057] S1. Preparation of modified basic magnesium sulfate whiskers

[0058] S1.1. Mix anhydrous ethanol and deionized water in a volume ratio of 2:1 to prepare a mixed solution as a modified solvent.

[0059] S1.2. Add 30% of silane coupling agent based on the mass of ordinary basic magnesium sulfate whisker (400 mesh) to 200 mL of modified solvent, and after ultrasonic dispersion for 30 minutes, use anhydrous oxalic acid to adjust the pH to about 4.5, and then add basic magnesium sulfate whisker (400 mesh). After ultrasonic dispersion for 2 hours, transfer to a 500 mL flask, condense and reflux at 65°C at a speed of 600 r / min for 3 hours to obtain a milky white gel liquid.

[0060] S1.3. Wash and purify the milky white gel liquid with anhydrous ethanol to remove unreacted coupling agent, then filter it and dry it in a constant temperature box at 60°C for 24 hours. Put the dried powder, grinding balls and water in a ball mill at a mass ratio of 1:1:0.5 for wet grinding for 2 hours at a speed of 600r / min. After grinding, take it out and pass it through a 1500 mesh sieve to obtain modified basic magnesium sulfate whiskers.

[0061] S2. Preparation of calcined magnesium aluminum carbonate type hydrotalcite

[0062] The magnesium aluminum carbonate type hydrotalcite was dried in an oven at 105°C for 24 hours, then placed in a muffle furnace, heated to 500°C at a heating rate of 20°C / min and kept at a constant temperature for 4 hours, and after cooling to room temperature with the furnace, the powder, grinding balls and water were put into a ball mill at a mass ratio of 1:1:0.5, wet-milled for 3 hours at a rotation speed of 600r / min, and taken out after grinding and passed through a 1000-mesh sieve to obtain calcined magnesium aluminum carbonate type hydrotalcite.

[0063] S3. Preparation of acid corrosion resistant materials

[0064] The modified basic magnesium sulfate whisker prepared by S1, the calcined magnesium aluminum carbonate type hydrotalcite prepared by S2, silicon carbide fiber and latex powder are uniformly mixed to obtain an acid corrosion resistant material.

[0065] The above-mentioned acid corrosion resistant material for cementing is used to prepare cement slurry for cementing.

[0066] The preparation of cement slurry for cementing is as follows: 100 parts of oil well cement and 3 parts of acid corrosion resistant material are mixed evenly to obtain a dry powder mixture; 44 parts of water are weighed, 0.2 parts of dispersant USZ, 0.2 parts of fluid loss reducer G33S, 0.1 parts of defoamer, and 0.1 parts of retarder are added, and the water is first poured into the stirring cup of the constant speed stirrer, and the speed is set to 1500r / min, and stirred at a low speed for 15s. During this period, the dry powder mixture, dispersant, fluid loss reducer, defoamer and retarder are slowly and evenly poured in, and then the speed is adjusted to 4000r / min, and stirred at a medium speed for 45s. Finally, the speed is adjusted to 6000r / min, and stirred at a high speed for 30s. After the stirring is completed, the slurry is prepared to obtain cement slurry for cementing that resists acid gas corrosion.

[0067] Example 3

[0068] The invention provides an acid corrosion resistant material for cementing, comprising 1000-mesh modified basic magnesium sulfate whisker, 2000-mesh calcined magnesium aluminum carbonate type hydrotalcite, 1000-mesh silicon carbide fiber, 1000-mesh latex powder and 2000-mesh nano silicon dioxide powder in a mass ratio of 2:1:2:1:1.

[0069] The method for preparing the above-mentioned acid corrosion resistant material for cementing comprises the following steps:

[0070] S1. Preparation of modified basic magnesium sulfate whiskers

[0071] S1.1. Mix anhydrous ethanol and deionized water in a volume ratio of 5:1 to prepare a mixed solution as a modified solvent.

[0072] S1.2. Add 50% of silane coupling agent based on the mass of ordinary basic magnesium sulfate whisker (500 mesh) to 200 mL of modified solvent, and after ultrasonic dispersion for 30 minutes, use anhydrous oxalic acid to adjust the pH to about 4.5, and then add basic magnesium sulfate whisker (500 mesh). After ultrasonic dispersion for 3 hours, transfer to a 500 mL flask, condense and reflux at 65°C at a speed of 800 r / min for 3 hours to obtain a milky white gel liquid.

[0073] S1.3. Wash and purify the milky white gel liquid with anhydrous ethanol to remove unreacted coupling agent, then filter it and dry it in a constant temperature box at 60°C for 24 hours. Put the dried powder, grinding balls and water in a ball mill at a mass ratio of 1:1:0.5 for 3 hours at a speed of 600r / min. After grinding, take it out and pass it through a 2000-mesh sieve to obtain modified basic magnesium sulfate whiskers.

[0074] S2. Preparation of calcined magnesium aluminum carbonate type hydrotalcite

[0075] The magnesium aluminum carbonate type hydrotalcite was dried in an oven at 105°C for 24 hours, then placed in a muffle furnace, heated to 500°C at a heating rate of 10°C / min and kept at a constant temperature for 2 hours, and after cooling to room temperature with the furnace, the powder, grinding balls and water were put into a ball mill at a mass ratio of 1:1:0.5, wet-milled for 2 hours at a speed of 800r / min, and taken out after grinding and passed through a 2000-mesh sieve to obtain calcined magnesium aluminum carbonate type hydrotalcite.

[0076] S3. Preparation of acid corrosion resistant materials

[0077] The modified basic magnesium sulfate whisker prepared by S1, the calcined magnesium aluminum carbonate type hydrotalcite prepared by S2, silicon carbide fiber and latex powder are uniformly mixed to obtain an acid corrosion resistant material.

[0078] The above-mentioned acid corrosion resistant material for cementing is used in preparing cement slurry for cementing.

[0079] The preparation of cement slurry for cementing is as follows: 100 parts of oil well cement and 5 parts of anti-acid corrosion material are mixed evenly to obtain a dry powder mixture; 44 parts of water are weighed, 0.2 parts of dispersant USZ, 0.2 parts of fluid loss reducer G33S, 0.1 parts of defoamer, and 0.1 parts of retarder are added, and the water is first poured into the stirring cup of the constant speed stirrer, and the speed is set to 1500r / min, and stirred at a low speed for 15s. During this period, the dry powder mixture, dispersant, fluid loss reducer, defoamer and retarder are slowly and evenly poured in, and then the speed is adjusted to 4000r / min, and stirred at a medium speed for 45s. Finally, the speed is adjusted to 6000r / min, and stirred at a high speed for 30s. After the stirring is completed, the slurry is prepared to obtain cement slurry for cementing that resists acid gas corrosion.

[0080] Comparative Example 1

[0081] A common cement slurry comprises, by weight, 100 parts of oil well cement, 0.2 parts of dispersant USZ, 0.5 parts of fluid loss reducer G33S, 0.1 parts of defoamer, 0.1 parts of retarder and 44 parts of clean water.

[0082] The preparation of ordinary cement slurry is as follows: take 100 parts of oil well cement, 44 parts of water, 0.2 parts of dispersant, 0.5 parts of fluid loss agent, 0.1 parts of defoamer and 0.1 parts of retarder, first pour the water into the mixing cup of the constant speed stirrer, set the speed to 1500r / min, stir at low speed for 15s, during which time slowly and evenly pour the oil well cement, dispersant, fluid loss agent, defoamer and retarder, then adjust the speed to 4000r / min, stir at medium speed for 45s, and finally adjust the speed to 6000r / min, stir at high speed for 30s, and end the stirring. The slurry preparation is completed, and an ordinary cement slurry is obtained.

[0083] Performance Testing

[0084] SEM Testing

[0085] The cement slurry prepared in Examples 1-3 and the ordinary cement slurry prepared in Comparative Example 1 were mixed with cement samples according to GB / T19139-2012 standard, cured at 55°C and normal pressure for 7 days, and then corroded for 60 days in an environment with a total pressure of 35MPa, a CO2 partial pressure of 15MPa, and a H2S partial pressure of 3MPa. The cement samples cured for 7 days and the inner and outer layer samples corroded for 60 days were taken out and immersed in anhydrous ethanol for 3 days to stop hydration. After hydration was stopped, they were placed in a 60°C oven for 3 days to dry out the moisture, taken out and broken into small pieces, and tested with a scanning electron microscope (SEM). The test results are as follows: Figure 1-4 shown.

[0086] Depend on Figure 1-4 It can be seen that the morphology of the cement samples of Examples 1-3 and Comparative Example 1 after curing for 7 days at 55°C is not much different, both of which are porous, and hydration products such as Ca(OH)2 can be seen. After 60 days of corrosion, the morphology of the cement stone becomes loose, the pores increase, and the pore diameter expands, especially the outer layer sample, the CaCO3 content increases significantly, but compared with Comparative Example 1, the morphology of the cement stone of Examples 1-3 after 60 days of corrosion is obviously denser, and the surface of the cement stone after corrosion is wrapped with a membrane-like substance, with a small amount of micropores, but its integrity is well maintained. It shows that by adding the anti-acid corrosion material of the present invention to the cement slurry, the corrosion performance of the cement slurry is significantly improved.

[0087] Permeability and Porosity Testing

[0088] The cement slurry for cementing prepared in Examples 1-3 and the ordinary cement slurry prepared in Comparative Example 1 were mixed with cement samples according to GB / T19139-2012 standard, and cured to form columnar cement stone samples with a diameter of 25 mm and a length of 300 mm. After curing for 7 days at 55°C and normal pressure, they were placed in an environment with a total pressure of 35 MPa, a CO2 partial pressure of 15 MPa, and a H2S partial pressure of 3 MPa for corrosion for 60 days. The samples after corrosion for 60 days were taken out and immersed in anhydrous ethanol for 3 days to stop hydration. After hydration was stopped, they were placed in a 60°C oven for 3 days to dry out the moisture. After being taken out, the permeability and porosity of the cement stone were tested. The pore size parameters and permeability are shown in Table 1, and the pore size distribution curve is shown in Figure 5 shown.

[0089] Table 1 Pore parameters and permeability of cement paste after 60 days of corrosion

[0090] ;

[0091] Mechanical properties test

[0092] The cement slurry for cementing prepared in Examples 1-3 and the ordinary cement slurry prepared in Comparative Example 1 were placed in a high-pressure water bath at 55°C and 21MPa for 7 days to form (cement stone), and the compressive strength was tested as a reference. The formed samples were placed in a corrosion kettle at 55°C, a total pressure of 35MPa, a CO2 partial pressure of 15MPa, and a H2S partial pressure of 3MPa to conduct a corrosion experiment. The compressive strength test before and after corrosion was performed, and the results are shown in Table 2.

[0093] Table 2 Compressive strength of cement paste before and after corrosion (MPa)

[0094] ;

[0095] Combined with Table 1-2 and Figure 5 It can be seen that the porosity and permeability of the cement stone of Examples 1-3 and Comparative Example 1 after 60 days of corrosion are negatively correlated with their compressive strength. The cement stone of Comparative Example 1 has a looser structure, which is caused by the destruction of the CSH structure in the cement stone by CO2. Under the action of CO2, the CSH in the cement stone is continuously dissolved, the porosity of the cement stone continues to increase, and H2S dissolves in water to generate calcium sulfate dihydrate (CaSO4·2H2O), which causes the volume of the cement stone to expand and crack, making it easier for the corrosive medium to enter the interior of the cement stone and continue to erode. The ordinary cement slurry system of Comparative Example 1 has not only the highest porosity, but also the highest strength decay rate. Compared with Comparative Example 1, the porosity and median pore size of the cement slurry for cementing in Examples 1-3 of the present invention are significantly reduced. The porosity of the cement slurry system in Example 2 is the lowest, which is 18.78%, and the median pore size is also at a relatively low level.

[0096] It can be seen from Table 2 that the corrosion resistance of the cement slurry for cementing prepared in Examples 1-3 of the present invention is significantly better than that of Comparative Example 1, which proves that after the anti-acid corrosion material provided by the present invention is used to prepare cement slurry for cementing, it does not affect its compressive strength while significantly improving the corrosion resistance of the cement slurry to carbon dioxide and hydrogen sulfide acid gases.

[0097] Comprehensive performance test

[0098] The cement slurries prepared in Examples 1-3 and the ordinary cement slurry prepared in Comparative Example 1 were tested for fluidity, density, free liquid, water loss and thickening time of the cement slurries respectively according to the national standard GB / T 19139-2012. The test results are shown in Table 3.

[0099] Table 3 Comprehensive performance data of cement slurry system

[0100] ;

[0101] As shown in Table 3, the cement slurries prepared in Examples 1-3 of the present invention have better stability than the ordinary cement slurry in Comparative Example 1, and the upper and lower density differences are ≤0.04 g / cm 3 , short thickening time, water loss ≤50 mL, and the comprehensive performance of the cement slurry system meets the requirements of cementing construction.

[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. An acid corrosion resistant material for cementing, characterized in that: The invention comprises modified basic magnesium sulfate whisker, calcined magnesium aluminum carbonate type hydrotalcite, silicon carbide fiber and a binder in a mass ratio of 1-2:0.5-1:1-2:1-2, wherein the binder is one or two of nano silicon dioxide powder and latex powder; The method for preparing the acid corrosion resistant material for cementing comprises the following steps: S1. Preparation of modified basic magnesium sulfate whiskers S1.1, mixing anhydrous ethanol and deionized water to prepare a mixed solution as a modified solvent; S1.2, add silane coupling agent to the modified solvent, ultrasonically disperse for 30 minutes, adjust the pH with anhydrous oxalic acid, then add basic magnesium sulfate whiskers, ultrasonically disperse for 2 to 3 hours, and heat the reaction to obtain a milky white gel liquid; S1.3, washing, purifying and drying the milky white gel liquid with anhydrous ethanol, grinding and sieving the dried powder to obtain modified basic magnesium sulfate whiskers; S2. Preparation of calcined magnesium aluminum carbonate type hydrotalcite The magnesium aluminum carbonate type hydrotalcite is dried in an oven, and then transferred to a muffle furnace for calcination. After cooling to room temperature in the furnace, the calcined magnesium aluminum carbonate type hydrotalcite is obtained by ball milling and sieving. S3. Preparation of acid corrosion resistant materials The modified basic magnesium sulfate whisker prepared by S1, the calcined magnesium aluminum carbonate type hydrotalcite prepared by S2, silicon carbide fiber and a binder are uniformly mixed to obtain an acid corrosion resistant material.

2. The acid corrosion resistant material for cementing according to claim 1, characterized in that: The particle size of the modified basic magnesium sulfate whisker is 1000-2000 meshes, the particle size of the calcined magnesium aluminum carbonate type hydrotalcite is 1000-2000 meshes, the particle size of the silicon carbide fiber is 1000-2000 meshes, and the particle size of the binder is 1000-2000 meshes.

3. A method for preparing the acid corrosion resistant material for cementing according to any one of claims 1 to 2, characterized in that: The following steps are included: S1. Preparation of modified basic magnesium sulfate whiskers S1.1, mixing anhydrous ethanol and deionized water to prepare a mixed solution as a modified solvent; S1.2, add silane coupling agent to the modified solvent, ultrasonically disperse for 30 minutes, adjust the pH with anhydrous oxalic acid, then add basic magnesium sulfate whiskers, ultrasonically disperse for 2 to 3 hours, and heat the reaction to obtain a milky white gel liquid; S1.3, washing, purifying and drying the milky white gel liquid with anhydrous ethanol, grinding and sieving the dried powder to obtain modified basic magnesium sulfate whiskers; S2. Preparation of calcined magnesium aluminum carbonate type hydrotalcite The magnesium aluminum carbonate type hydrotalcite is dried in an oven, and then transferred to a muffle furnace for calcination. After cooling to room temperature in the furnace, the calcined magnesium aluminum carbonate type hydrotalcite is obtained by ball milling and sieving. S3. Preparation of acid corrosion resistant materials The modified basic magnesium sulfate whisker prepared by S1, the calcined magnesium aluminum carbonate type hydrotalcite prepared by S2, silicon carbide fiber and a binder are uniformly mixed to obtain an acid corrosion resistant material.

4. The method for preparing the acid corrosion resistant material for cementing according to claim 3, characterized in that: The volume ratio of anhydrous ethanol to deionized water in S1.1 is 2 to 5:

1.

5. The method for preparing the acid corrosion resistant material for cementing according to claim 3, characterized in that: The amount of silane coupling agent in S1.2 is 30% to 50% of the mass of the basic magnesium sulfate whisker, the pH range is 4.0 to 5.0, and the heating reaction is condensed and refluxed at a temperature of 65°C and a speed of 500-800r / min for 3h.

6. The method for preparing the acid corrosion resistant material for cementing according to claim 3, characterized in that: In S1.3, the drying is carried out in a thermostatic box at 60°C for 24 hours, the grinding is carried out in a ball mill for 2 to 3 hours, the rotation speed is 600-800r / min, the mass ratio of powder, balls and water in the ball mill is 1:1:0.5, and the sieving is carried out through a sieve of 1000-2000 mesh.

7. The method for preparing the acid corrosion resistant material for cementing according to claim 3, characterized in that: In S2, the oven drying is performed at 105°C for 24 hours, and the calcination is performed in a muffle furnace at a heating rate of 10 to 20°C / min, rising to 500°C and maintaining the temperature for 2 to 4 hours.

8. The method for preparing the acid corrosion resistant material for cementing according to claim 3, characterized in that: The ball milling in S2 is wet grinding in a ball mill for 2 to 3 hours, with a rotation speed of 600-800r / min, a mass ratio of powder, balls and water in the ball mill of 1:1:0.5, and screening is through a sieve of 1000-2000 mesh.

9. An application of the acid corrosion resistant material for cementing as claimed in any one of claims 1 to 2, characterized in that: Used in preparing cement slurry for cementing.

10. The use of the acid corrosion resistant material for cementing according to claim 9, characterized in that: The preparation of cement slurry for cementing is as follows: take oil well cement and anti-acid corrosion material and mix them evenly to obtain a dry powder mixture; weigh water, dispersant, fluid loss agent, defoamer, and retarder, first pour the water into the mixing cup of the constant speed stirrer, set the speed to 1500r / min, stir at low speed for 15s, during which time slowly and evenly pour the dry powder mixture, dispersant, fluid loss agent, defoamer and retarder, then adjust the speed to 4000r / min, stir at medium speed for 45s, and finally adjust the speed to 6000r / min, stir at high speed for 30s, end the stirring, and the slurry preparation is completed.